LEADERSHIP OF SCHOOL ADMINISTRATORS IN THE 21ˢᵗ CENTURY THAT AFFECTING TEACHER’S INSPIRATION OF PERFORM UNDER NAKHON SI THAMMARAT PRIMARY EDUCATIONAL SEVICE AREA 4 - archachan, Orapan; Chanakul, Benchaporn; Temrat, Suparp (Journal of MCU Nakhondhat, 2023)
The purpose of this research is to study 1) Leadership of School Administrators in the 21 Century 2) Teacher Performance Inspiration 3) The leadership of school administrators in the 21 th century that affects teachers’ motivation for performance. and 4) Leadership Development Guidelines for School Administrators in the 21Century That Affect Teachers’ Performance Aspirations Nakhon Si Thammarat Primary Education Area Office District 4 The research methodology is descriptive research at a particular point in time (Cross-sectional Descriptive Studies) The subjects in this study were school administrators and teachers 388 people Research instruments include: questionnaire It has a total sentiment value of 0.92. Statistics used to analyze data include: Frequency, percentage, average, standard deviation Analysis of Pearson’s correlation coefficient and content analysis The results of the research were as follows: 1) Leadership of School Administrators in the 21 Century overall and individual aspects are at a large level. 2)Teacher Performance Inspiration overall to a large extent.3 The leadership of school administrators in the 21 th century that affects teachers’ motivation for performance Affiliated with Nakhon Si Thammarat Primary Education Area Office District 4 consist: Creativity and emotional intelligence It can contribute 9.30 percent statistically significant at the .05 level. 4) Leadership Development Guidelines for School Administrators in the 21 Century That affects teachers’ motivation for performance Nakhon Si Thammarat Primary Education Area Office District 4 consist: 1) Innovation and Information Technology in Education 2) Vision includes: Executives must have genuine leadership. Executives must have skills. 3) creativity and 4) Emotional intelligence